Maxillo-mandibular counter-clockwise rotation and mandibular advancement with TMJ Concepts (R) total joint prostheses Part III - Pain and dysfunction outcomes - Pinto, L. P.; Wolford, L. M.; Buschang, P. H.; Bernardi, F. H.; Gonçalves, João Roberto [UNESP]; Cassan, D. S. (Churchill Livingstone, 2009)
47 end-stage TMJ patients with high occlusal plane angulation, treated with TMJ custom-fitted total joint prostheses and simultaneous maxillo-mandibular counter-clockwise rotation were evaluated for pain and dysfunction presurgery (T1) and at the longest follow-up (T2). Patients subjectively rated their facial pain/headache, TMJ pain, jaw function, diet and disability. Objective functional changes were determined by measuring maximum interincisal opening (MIO) and laterotrusive movements. Patients were divided according to the number of previous failed TMJ surgeries: Group 1 (0-1), Group 2 (2 or more). Significant subjective pain and dysfunction improvements (37-52%) were observed (<0.001). MIO increased 14% but lateral excursion decreased 60%. The groups presented similar absolute changes, but Group 2 showed more dysfunction at T1 and T2. For patients who did not receive fat grafts around the prostheses and had previous failure of proplast/teflon and or silastic TMJ implants, more than half required surgery for TMJ debridement and removal of foreign body giant cell reaction and heterotopic bone formation. End-stage TMJ patients can be treated in one operation with TMJ custom-made total joint prostheses and maxillo-mandibular counter-clockwise rotation, for correction of dentofacial deformity and improvement in pain and TMJ dysfunction; Group 1 patients had better results than Group 2 patients.
Keywords: temporomandibular joint; TMJ reconstruction; custom-made total prosthesis; pain; dysfunction